Multicenter randomized double-blind placebo-controlled crossover study of the effect of prolonged noisy galvanic vestibular stimulation on posture or gait in vestibulopathy. - Chisato Fujimoto; Takuya Kawahara; Yayoi S Kikkawa; Makoto Kinoshita; Teru Kamogashira; Mineko Oka; Tsukasa Uranaka; Naoya Egami; Kentaro Ichijo; Kayoko Kabaya; Sachiyo Katsumi; Ikumi Takashima; et al. (PLoS ONE)
Objective This multicenter, randomized, double-blind, placebo-controlled, crossover trial aimed to evaluate whether prolonged noisy galvanic vestibular stimulation improves body balance in patients with vestibulopathy. Materials and methods This trial was registered in the Japan Pharmaceutical Information Center Clinical Trials Information registry (jRCT1080224083). Subjects were 20- to 85-year-old patients who had been unsteady for more than one year and whose symptoms had persisted despite more than six months of rehabilitation. Enrolled subjects were randomly assigned to one of two groups; one group received the optimal intensity of noisy galvanic vestibular stimulation first and then the placebo 14 days later, the other was evaluated in the reverse order. The primary outcome was the difference of the mean percent change from the baseline in the velocity of center of pressure during 3 h of stimulation between the noisy galvanic vestibular stimulation and placebo periods. This was analyzed with the mixed effects model. Results Forty-two subjects were enrolled. The mean percent change in the velocity during stimulation for 3 h was -9.3% (SD 19.9%) for noisy galvanic vestibular stimulation and -12.6% (SD 15.0%) for placebo. No significant effects of noisy galvanic vestibular stimulation over placebo were found for velocity in the least-squares means of the difference [3.1% (95% CI -0.2 to 6.4, p = 0.066)]. Conclusion Prolonged noisy galvanic vestibular stimulation did not significantly improve body balance in patients with poorly-compensated vestibulopathy.